The holy vote: inequality and anxiety among white evangelicals - Diefendorf, Sarah H. (University of California Press, 2023)
Through two years of ethnographic fieldwork at a megachurch, sociologist Sarah Diefendorf investigates the ways in which the evangelical church is working to grow during a time in which cultural shifts are leading young people to leave religion behind. In order to expand, the church has revisited topics long understood as external threats to the organization, such as feminism, gender equality, racial inclusivity, and queer life—topics Diefendorf classifies as the “imagined secular” in the minds of evangelicals.The Holy Vote shows, however, that the church continues to uphold already privileged identities even as it reworks its messages to appear more welcoming, offering insight into how White evangelical understandings about sex and families have shaped a political movement that has helped remake the Republican Party and transform American politics. In this enlightening work, Diefendorf highlights the complex origins of these understandings and considers their intersections with contemporary culture and enduring social inequalities